A zinc amino acid complex crystal material and its preparation method and application
By designing the synthetic Zn complex (NCLA-Zn) as a fluorescence recognition sensor, the problems of low sensitivity and high cost of Fe3+ detection in the prior art are solved, and the effect of rapid, sensitive and selective detection of Fe3+ is achieved, and the recognition effect on antibiotics is achieved.
Patent Information
- Application Number
- CN202411782909.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The prior art has problems of low sensitivity, low selectivity and high cost when detecting Fe3+, and lacks portable and low-cost Fe3+ detection sensors.
The Zn complex (NCLA-Zn) that can be used to quickly identify Fe3+ was accurately designed and synthesized by the hybrid ligand method. As a new fluorescence recognition sensor, this material can quickly detect Fe3+ and have a recognition effect on antibiotics.
It realizes fast, sensitive and selective detection of Fe3+, and is low in cost. It is suitable for use in the fields of quality inspection and environmental protection, improving the maintenance capabilities of food quality, safety and environmental health.
Smart Images

Figure CN119264459B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of crystalline materials, and the technology relates to metal-organic coordination polymer materials, and in particular to a zinc amino acid complex crystal material, a preparation method and application thereof. Background Art
[0002] Fe(III) is a typical nutrient that plays a vital role in various physiological and biochemical functions in organisms at low concentrations. For example, it is one of the most essential elements in the processes of hemoglobin formation, DNA synthesis, oxygen storage, etc. But when the concentration exceeds a certain threshold, it becomes harmful and causes poisoning, leading to serious physiological disorders such as insomnia, decreased immunity, gastrointestinal disorders, and cirrhosis. According to the World Health Organization (WHO) guidelines on drinking water quality, the maximum allowable limit of iron is 0.3 mg / L. However, with the rapid development of industry, improper operation or handling has occurred, and iron has become an important source of inorganic pollutants. For example, in industry, a large amount of Fe 3+ The wastewater is directly discharged into rivers; in agricultural production, excessive use of iron-containing fertilizers and pesticides can also lead to Fe 3+ Increased concentrations affect plant growth and even enter the human body through the food chain. 3+ The importance and impact of Fe in biological and environmental systems, therefore, the environmental Fe 3+ The detection of concentration is very important. The main analytical methods currently include high performance liquid chromatography (HPLC), capillary electrophoresis (CE), mass spectrometry (MS), etc. These methods are often complex and time-consuming, with low sensitivity, low selectivity and high actual application costs. The development of highly sensitive and rapid specific detection methods is of great research significance.
[0003] In recent years, there has been great interest in developing portable, low-cost Fe 3+ There is growing interest in Fe-based sensors. However, the specificity of these sensors needs to be further improved for practical applications, and more reproducible and easy-to-use Fe-based sensors need to be developed. 3+ Detection sensor. Fluorescence recognition has the advantages of low cost and fast analysis speed, and has become an ideal recognition method. Luminescent materials have potential application prospects in fluorescence recognition and sensing, and are expected to become portable detectors that can replace large instruments for recognition.
[0004] Antibiotics, as a drug that can inhibit and kill bacteria, have been widely used in medical and health care, livestock and poultry breeding, agricultural production and other industries, and have made great contributions to the economic development of society. However, most of the antibiotics taken by humans and animals cannot be fully absorbed by the body, but are metabolized outside the body and enter the environment. This will lead to the accumulation of antibiotics in the biosphere, which not only endangers the survival and reproduction of organisms and affects the function of ecosystems, but also has the risk of causing "super bacteria", posing a serious threat to the safety of the human living environment and life and health, so antibiotic detection methods are needed to regulate this phenomenon.
[0005] Coordination polymers (CPs), especially metal-organic frameworks (MOFs), are inorganic-organic hybrid materials based on metal ions / metal clusters and organic ligands that form one-dimensional, two-dimensional, and three-dimensional repeatable structural units through coordination bonds. Compared with traditional hybrid materials, metal-organic complexes use crystal engineering principles in design and synthesis. When designing the structure, ligands / functional groups with specific properties can be introduced into the framework structure, so that this type of material combines the characteristics of inorganic and organic components, and has the advantages of adjustable pore size and shape, special spatial topology, designability, high porosity and specific surface area, and low density. Among emerging materials, CPs have developed into a new type of luminescent sensor for rapid detection of metal ions, anions, organic solvents, antibiotics, carcinogens, etc. The main reasons are as follows: First, the structure and properties of CPs can be controlled by rationally and wisely selecting different types of ligands, metal ions, and their effective combinations. Second, CPs as luminescent sensors usually have very high sensitivity. Third, the operation is simple and the cost is low. Finally, most CPs are recyclable and have multiple uses as luminescent sensors. Based on this, the present invention is guided by functional applications and uses a mixed ligand method to accurately design and synthesize a ligand that can be used to quickly identify Fe 3+ The NCLA-Zn prepared by the present invention is a new type of fluorescence recognition sensor that can quickly detect Fe 3+ In addition, the recognition effect of NCLA-Zn on antibiotics was also studied. The results showed that the probe had a certain recognition effect on antibiotics such as doxycycline, minocycline hydrochloride, etc. This material can be used in quality inspection, environmental protection and other fields, and is of great significance for improving food quality and safety and maintaining environmental health. Summary of the invention
[0006] One of the purposes of the present invention is to provide a zinc amino acid complex crystalline material, the chemical formula of which is [Zn(bib)(NCLA)] n , hereinafter named NCLA-Zn, wherein bib is the auxiliary ligand 1,4-bis(1-imidazolyl)benzene (CAS No.: 25372-07-0), and the chemical structure is as follows:
[0007] ;
[0008] NCLA is deprotonated N-benzyloxycarbonyl-L-aspartic acid (CAS No.: 1152-61-0). The chemical structure of N-benzyloxycarbonyl-L-aspartic acid is shown below:
[0009] .
[0010] Furthermore, from the perspective of framework connection construction, the crystal structure of the zinc amino acid complex crystal material NCLA-Zn belongs to the monoclinic system. C 2 space group, unit cell parameters are: a=20.023(3) Å, b=10.9307(15) Å, c=15.053(2) Å, α =90°, β = 128.961(3)°, γ =90°.
[0011] Furthermore, in NCLA-Zn, an asymmetric unit contains a Zn(II), a NCLA 2- ligand and a bib ligand;
[0012] The coordination number of Zn(II) is 4, and each Zn(II) is bound to two NCLA 2- The two oxygen atoms in the ligand are O6 and O4 i and the two N atoms N2 and N5 in the two bib ligands ii Coordination; each NCLA 2- The two oxygen atoms O6 and O4 of the ligand connect to two different Zn(II); the two N atoms N2 and N5 of each bib ligand connect to two different Zn(II) respectively;
[0013] Along the b-axis, adjacent Zn(II) are connected by NCLA 2- O6 and O4 on the ligand are connected to form a 1D chain. The two adjacent 1D chains are arranged symmetrically. Two adjacent bib ligands are connected to the adjacent 1D chains through cross-linking. Through the above connection method, they extend infinitely in the b-axis direction to form a two-dimensional layered structure. The two-dimensional layered structure is stacked with each other through intermolecular hydrogen bonding interactions C6—H6···O2 and C22—H22···O2 to form a 3D framework.
[0014] Furthermore, from a topological point of view, Zn(II) can serve as a 4-junction point, and each NCLA 2-The bib ligand connects two Zn(II), so the two ligands can be simplified to a 2-linker. According to TOPOS software calculation, the Schläfli symbol of the NCLA-Zn is {4 2 6 3 ·8}.
[0015] Furthermore, the Zn1-O bond lengths are 1.950(5)Å and 1.953(4)Å, and the Zn1-N bond lengths are 2.014(5)Å and 2.019(5)Å;
[0016] The present invention also provides a method for preparing the zinc amino acid complex crystal material, comprising the following steps:
[0017] The metal salt ZnCl2, the main ligand N-benzyloxycarbonyl-L-aspartic acid and the auxiliary ligand bib were weighed and placed in a closed container, and a mixed solution of CH3OH and H2O was added to carry out a heating reaction. After the system slowly cooled to room temperature, a white block complex NCLA-Zn was obtained.
[0018] Further, the molar ratio of ZnCl2 to N-benzyloxycarbonyl-L-aspartic acid is 1:(1-1.5);
[0019] The molar ratio of ZnCl2 to bib is 1:(1.23-1.85).
[0020] Furthermore, the volume ratio of CH3OH / H2O in the mixed solution of CH3OH and H2O is 1: (1-1.25), and the volume of the mixed solution is limited to 9 ml of the mixed solution for every 0.1 mmol of ZnCl2.
[0021] Furthermore, the heating temperature is 85-100° C., and the reaction time is 48-84 hours.
[0022] The invention also provides application of the zinc amino acid complex crystal material in solvent recognition.
[0023] Furthermore, the zinc amino acid complex crystal material has different fluorescence intensities in different solvents.
[0024] The present invention also provides the zinc amino acid complex crystal material in identifying Fe 3+ Application in.
[0025] Furthermore, the zinc amino acid complex crystal material contains Fe 3+ In the solution, fluorescence quenching occurs.
[0026] The invention also provides application of the zinc amino acid complex crystal material in identifying antibiotics.
[0027] Furthermore, when doxycycline was added to the zinc amino acid complex crystal material, the fluorescence intensity was quenched by 91.8%; when minocycline hydrochloride was added, the fluorescence intensity was quenched by 89.8%.
[0028] Beneficial technical effects of the present invention:
[0029] The zinc amino acid complex crystal material of the present invention has a novel structure, and the deprotonated ligand NCLA 2- The two carboxyl groups -COO- in the molecule simultaneously connect Zn(II) to form a chain structure, and the adjacent chains are connected by cross-bib ligands to form a 2D layered structure. There are weak intermolecular hydrogen bonds between the 2D layers, forming a three-dimensional framework structure.
[0030] The zinc amino acid complex crystal material of the present invention can be used to identify solvent molecules, metal ions and antibiotics. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the coordination environment of Zn(II) in NCLA-Zn (symmetry code i -x+1.5, y-0.5, -z+1; ii x+0.5, y+0.5, z+1).
[0032] Figure 2 For adjacent Zn(II) and NCLA 2- The ligands are linked along the b-axis to form a 1D chain.
[0033] Figure 3 It is a two-dimensional layered structure of NCLA-Zn.
[0034] Figure 4 It is the three-dimensional framework structure of NCLA-Zn.
[0035] Figure 5 Schematic diagram of hydrogen bonds in the NCLA-Zn structure.
[0036] Figure 6 This is the topological structure diagram of NCLA-Zn.
[0037] Figure 7 This is the infrared spectrum of NCLA-Zn.
[0038] Figure 8 This is the thermogravimetric analysis diagram of NCLA-Zn.
[0039] Fig. 9 It is the solid-state emission spectrum diagram of NCLA-Zn and its ligand of the present invention.
[0040] Fig.10 1 is the fluorescence emission spectrum of NCLA-Zn of the present invention in different solvents.
[0041] Fig.11 This is the fluorescence emission spectrum of NCLA-Zn of the present invention in Fe(NO3)3, NaNO3, KNO3, Al(NO3)3, Cr(NO3)2, Mn(NO3)2, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, Zn(NO3)2, AgNO3, Cd(NO3)2, and Pb(NO3)2 solutions.
[0042] Fig.12 This is a bar graph of the emission peak intensity of NCLA-Zn of the present invention near 310 nm in Fe(NO3)3, NaNO3, KNO3, Al(NO3)3, Cr(NO3)2, Mn(NO3)2, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, Zn(NO3)2, AgNO3, Cd(NO3)2, and Pb(NO3)2 solutions.
[0043] Fig.13 It is the fluorescence emission spectrum of NCLA-Zn of the present invention in antibiotic solutions such as nitrofurantoin, erythromycin, nitrofuracil, sulfamethoxazole sodium, chloramphenicol, tetracycline, metronidazole, florfenicol, sulfadiazine, oxytetracycline, dimetridazole, amoxicillin, sulfathiazole, sulfamethoxazole, methacycline hydrochloride, minocycline hydrochloride, and doxycycline.
[0044] Fig.14 The figure is a bar graph of the emission peak intensity of NCLA-Zn of the present invention near 310 nm in nitrofurantoin, erythromycin, nitrofuracil, sulfamethoxazole sodium, chloramphenicol, tetracycline, metronidazole, florfenicol, sulfadiazine, oxytetracycline, dimetridazole, amoxicillin, sulfathiazole, sulfamethoxazole, methacycline hydrochloride, minocycline hydrochloride, and doxycycline solutions.
[0045] Fig.15 The present invention NCLA-Zn in the non-rare earth metal ion Fe 3+ Bar graph of the intensity of the strongest emission peak in the competitive recognition experiment.
[0046] Fig.16 The NCLA-Zn of the present invention is Fe in the rare earth ion 3+ Bar graph of the intensity of the strongest emission peak in the competitive recognition experiment. DETAILED DESCRIPTION
[0047] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.
[0048] Example 1
[0049] ZnCl2 (13.63 mg, 0.1 mmol), the main ligand N-benzyloxycarbonyl-L-aspartic acid (27.43 mg, 0.1 mmol) and the auxiliary ligand bib (21.00 mg, 0.123 mmol) were placed in a 20.0 ml pressure-resistant thick glass sample bottle, and 9.0 ml of CH3OH / H2O (1: 1) solution was measured and placed in the above glass sample bottle. Finally, the sample bottle was sealed with a sample bottle cap, placed in a forced air drying oven, and heated at 90.0°C for 3 days to obtain white block crystals.
[0050] Example 2
[0051] ZnCl2 (13.63 mg, 0.1 mmol), the main ligand N-benzyloxycarbonyl-L-aspartic acid (27.43 mg, 0.1 mmol) and the auxiliary ligand bib (21.00 mg, 0.123 mmol) were placed in a 20.0 ml pressure-resistant thick glass sample bottle, and 9.0 ml of CH3OH / H2O (4: 5) solution was measured and placed in the above glass sample bottle. Finally, the sample bottle was sealed with a sample bottle cap, placed in a forced air drying oven, and heated at 90.0°C for 3 days to obtain white block crystals.
[0052] Example 3
[0053] ZnCl2 (13.63 mg, 0.1 mmol), the main ligand N-benzyloxycarbonyl-L-aspartic acid (41.14 mg, 0.15 mmol) and the auxiliary ligand bib (21.00 mg, 0.123 mmol) were placed in a 20.0 ml pressure-resistant thick glass sample bottle, and 9.0 ml of CH3OH / H2O (1: 1) solution was measured and placed in the above glass sample bottle. Finally, the sample bottle was sealed with a sample bottle cap, placed in a forced air drying oven, and heated at a constant temperature of 100.0°C for 48 minutes to obtain white block crystals.
[0054] Example 4
[0055] ZnCl2 (13.63 mg, 0.1 mmol), the main ligand N-benzyloxycarbonyl-L-aspartic acid (27.43 mg, 0.1 mmol) and the auxiliary ligand bib (31.50 mg, 0.185 mmol) were placed in a 20.0 ml pressure-resistant thick glass sample bottle, and 9.0 ml of CH3OH / H2O (1: 1) solution was measured and placed in the above glass sample bottle. Finally, the sample bottle was sealed with a sample bottle cap, placed in a forced air drying oven, and heated at 85.0°C for 84 minutes to obtain white block crystals.
[0056] The test results of the products obtained in the above embodiments are the same, as shown below:
[0057] (1) Crystal structure determination:
[0058] Crystals with better growth and fewer cracks were selected and glued to a thin glass wire. The diffraction data of NCLA-Zn were collected under Mo-Kα radiation (λ = 0.71073 Å) at room temperature using a BrukerAPEX-II CCD single crystal diffractometer. NCLA-Zn was refined using Shellxl-2015 in the OLEX2 program. The structure was solved using the XS structure solver, and the SHELXTL software package was used for least squares optimization. In the process of improvement, the anisotropic displacement parameters of non-hydrogen atoms were given. The positions of hydrogen atoms on the ligands were determined using the theoretical hydrogenation method. The crystallographic data are shown in Table 1.
[0059] Table 1 Crystallographic data of metal organic framework materials
[0060]
[0061] The structure of NCLA-Zn prepared in Example 1-4 is shown in Figure 1-Figure 4 As shown, Figure 1 is the coordination environment of Zn(II), where the coordination number of Zn(II) is 4, and each Zn(II) is respectively connected to two NCLA 2- The two oxygen atoms in the ligand are O6 and O4 i and the two N atoms N2 and N5 in the two bib ligands ii Coordination; each NCLA 2- The two oxygen atoms O6 and O4 of the ligand connect to two different Zn(II); the two N atoms N2 and N5 of each bib ligand connect to two different Zn(II) respectively.
[0062] Figure 2 For adjacent Zn(II) and NCLA 2- The ligands are connected along the b axis to form a 1D chain. Two adjacent 1D chains are arranged symmetrically. Two adjacent bib ligands are connected to adjacent 1D chains by cross-linking. Through the above connection method, they extend infinitely in the b axis direction to form a two-dimensional layered structure. Figure 3 ; The two-dimensional layered structures are stacked with each other through intermolecular hydrogen bonding interactions, C6—H6···O2 and C22—H22···O2, to form a 3D framework, see Figure 4 and Figure 5 .
[0063] Figure 6The simplified topological diagram of the framework structure shows that Zn(II) can act as a four-connector. At the same time, each NCLA 2- and bib ligands connecting two Zn(II)s, whose Schläfli symbol is {4 2 6 3 ·8}. From the topological diagram, we can see that the two adjacent 1D chains are symmetrically distributed.
[0064] The NCLA-Zn prepared in Examples 1-4 was characterized by infrared and thermogravimetric analysis using a Shimadzu FTIR-8400S spectrometer at 4000-500 cm −1 The FT-IR spectrum of NCLA-Zn was collected within the range of Figure 7 , the corresponding characteristic absorption peaks were characterized, and the results confirmed that -COOH participated in the coordination. The main absorption peaks of NCLA-Zn are as follows: 3428 (w), 3130 (m),1711 (w), 1621 (m), 1532 (s), 1502 (w), 1410 (w), 1312 (m), 1267(w),1141(w),1071(s), 963(m), 947 (w), 831(m), 760 (w), 647 (m), 534 (w), 503 (w).
[0065] Figure 8 The thermogravimetric analysis of NCLA-Zn shows that: According to thermogravimetric analysis, there is almost no weight loss before 235°C, indicating that the complex is very stable and can maintain the stability of the framework structure below 235°C. There are no free and coordinated solvent molecules, which is consistent with the molecular formula [Zn(bib)(NCLA)] in the single crystal analysis. n Good thermal stability is conducive to the application and promotion of NCLA-Zn.
[0066] Because based on d 10 Coordination polymers with transition metal centers have great potential applications in the research of luminescent sensors, photochemistry and electroluminescence. 2+ The fluorescence properties of the constructed coordination polymers have attracted much attention. Therefore, the solid-state fluorescence properties of NCLA-Zn were investigated at room temperature. Fig. 9 The solid-state fluorescence emission spectra of ZCLA-Zn and its ligands of the present invention are shown in the figure. It can be seen from the figure that when the excitation wavelength is 255 nm, the strongest emission peak of ZCLA-Zn is at 310 nm, and the luminescence of NCLA-Zn can be attributed to the π→π* electron transition inside the ligand. Compared with the free NCLA ligand, NCLA-Zn shows a red shift; compared with bib, NCLA-Zn shows a blue shift, which may be due to the interaction between the ligand and Zn 2+Caused by coordination.
[0067] In order to gain a deeper understanding of its fluorescence properties, two important luminescence parameters of fluorescent materials were tested: fluorescence lifetime and fluorescence quantum yield. Through testing combined with simulation calculations, the fluorescence lifetime of NCLA-Zn is about 1.6 nanoseconds, and the quantum yield of NCLA-Zn is 7.19%.
[0068] Furthermore, the fluorescence recognition effect of NCLA-Zn on different solvent molecules was tested. At room temperature, NCLA-Zn was added to different solvents such as water (H2O), N,N'-dimethylformamide (DMF), N,N'-diethylformamide (DEF), N,N'-dimethylacetamide (DMA), dimethyl sulfoxide (DMSO), acetonitrile (CH3CN), methanol (CH3OH), ethanol (CH3CH2OH), 1,4-dioxane (1,4-Dioxane), and N-pyrrolidone (NMP), and then ultrasonicated for 15 minutes to dissolve the crystal sample and obtain a suspension. The fluorescence spectrum was measured using a fluorescence spectrometer. For details, see Fig.10 The strongest emission peak of NCLA-Zn in different solvents is between 313 and 323 nm, with little change. However, the fluorescence intensity varies greatly, with the strongest emission peak in CH3CH2OH having the highest intensity and the lowest intensity in DEF. The specific order of fluorescence intensity is as follows: CH3CH2OH>CH3CN>CH3OH>1,4-Dioxane>H2O>NMP>DMA>DMSO>DMF>DEF.
[0069] Furthermore, CH3CH2OH was used as solvent to test the fluorescence recognition effect of NCLA-Zn on different metal ions. Under room temperature, Fe(NO3)3, NaNO3, KNO3, Al(NO3)3, Cr(NO3)2, Mn(NO3)2, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, Zn(NO3)2, AgNO3, Cd(NO3)2, Pb(NO3)2 and other metal salts were weighed to prepare 10 -3 M solution, NCLA-Zn was added to the above metal ion solution, and its fluorescence spectrum was measured using a fluorescence spectrometer. Fig.11 The strongest emission peak is located near 316 nm, but the fluorescence intensity changes greatly. + and K + After the addition of Fe, the fluorescence intensity was enhanced, but after the addition of other metal ions, the fluorescence intensity was weakened to varying degrees. 3+ In the solution of NCLA-Zn, the fluorescence quenching rate was as high as 99.8% compared with the blank sample.3+ Have obvious recognition ability. Fig.12 The bar chart shows the strongest emission peak intensity of NCLA-Zn in different metal ion solutions. The order of fluorescence intensity in different metal ions: K + >Na + >Blank Sample>Pb 2+ >Co 2+ >Ni 2+ >Zn 2+ >Cr 3+ >Mn 2+ >Al 3+ >Ag + >Cu 2+ >Fe 3+ .
[0070] Since Fe 3+ Monitoring is often interfered by other ions. The competitive experiment of different metal ions was used to test the effect of NCLA-Zn on Fe 3+ Anti-interference ability of detection. The specific implementation is as follows: By comparing the blank (complex + ethanol + iron ion) with the complex + ethanol + iron ion + other metal ions, observe whether other metal ions affect the recognition of iron ions. If the intensity of "complex + ethanol + iron ion + other metal ions" is very low, it means that NCLA-Zn has strong selectivity for iron ions and strong anti-interference ability.
[0071] Fig.15 The fluorescence emission spectrum of the competitive experiment of NCLA-Zn in metal ions of the present invention shows that: when Fe-containing 3+ After the mixed ions, the fluorescence intensity of NCLA-Zn decreased significantly, which was different from that of the sample with only Fe 3+ The time difference is not large, which proves that NCLA-Zn can achieve Fe 3+ Selective detection, strong selectivity and strong anti-interference ability.
[0072] Fig.16 The fluorescence emission spectrum of the competitive experiment of NCLA-Zn in rare earth ions of the present invention shows that: adding Fe 3+ After the mixed ions, the fluorescence intensity of NCLA-Zn decreased significantly, which was different from that of the sample with only Fe 3+ The time difference is not large, which proves that NCLA-Zn can achieve Fe 3+ Selective detection, strong selectivity and strong anti-interference ability.
[0073] Furthermore, the fluorescence recognition of antibiotics by NCLA-Zn was determined using CH3CH2OH as solvent.
[0074] Weigh nitrofurantoin, erythromycin, nitrofuracil, sulfadiazine sodium, chloramphenicol, tetracycline, metronidazole, florfenicol, sulfadiazine, oxytetracycline, dimetridazole, amoxicillin, sulfathiazole, sulfamethoxazole, methacycline hydrochloride, minocycline hydrochloride, doxycycline and other antibiotics to prepare 10 -4 M solution, NCLA-Zn was added to the ethanol solution of the above antibiotics, and the fluorescence emission spectra of NCLA-Zn in different antibiotic solutions were measured. The results are shown in Fig.13 , the position of the strongest emission peak changes with different antibiotics, and the fluorescence intensity also changes significantly. When the excitation wavelength is 255nm, the strongest emission peak is between 310-340 nm. Among them, the strongest emission peak of the blank sample is still around 310nm. Compared with the blank, the strongest peak red-shifts after adding some antibiotics. Among them, the strongest emission peaks of amoxicillin, chloramphenicol, sulfamethoxazole, and sulfadiazine are around 319nm, the strongest emission peak of sulfathiazole is at 322nm, the strongest emission peak of metronidazole is at 327nm, and the strongest emission peak of dimetridazole is around 340nm. However, the intensity changes of the strongest emission peaks of each system are more obvious. For details, see Fig.14 When florfenicol and erythromycin were added, the fluorescence intensity was minimal compared with the blank sample, but the addition of other antibiotics caused the fluorescence intensity to be quenched to varying degrees. The specific fluorescence intensity of the strongest emission peak was in the following order: florfenicol ≈ blank sample > erythromycin > amoxicillin > chloramphenicol > metronidazole ≈ sulfadiazine ≈ sulfamethoxazole > nitrofurantoin > dimetridazole > sulfathiazole > oxytetracycline ≈ nitrofurantoin > sulfadiazine sodium > mefenamic acid hydrochloride > tetracycline > minocycline hydrochloride > doxycycline. After doxycycline was added, the fluorescence intensity was quenched by 91.8%; after minocycline hydrochloride was added, the fluorescence intensity was quenched by 89.8%; after mefenamic acid hydrochloride was added, the fluorescence intensity was quenched by 88.2%; after tetracycline was added, the fluorescence intensity was quenched by 85.6%. This shows that NCLA-Zn has a good recognition effect on doxycycline and minocycline hydrochloride.
Claims
1. A zinc amino acid complex crystal material, characterized in that: The chemical formula is [Zn(bib)(NCLA)] n , hereinafter named NCLA-Zn, wherein bib is the auxiliary ligand 1,4-bis(1-imidazolyl)benzene, and the chemical structure is as follows: ; NCLA is deprotonated N-benzyloxycarbonyl-L-aspartic acid, and its chemical structure is shown below: ; The asymmetric unit in the NCLA-Zn crystal structure comprises a Zn(II), a NCLA 2- ligand and a bib ligand; The coordination number of Zn(II) is 4, and each Zn(II) is bound to two NCLA 2- The two oxygen atoms in the ligand are O6 and O4 i and the two N atoms N2 and N5 in the two bib ligands ii Coordination; each NCLA 2- The two oxygen atoms O6 and O4 of the ligand connect to two different Zn(II); the two N atoms N2 and N5 of each bib ligand connect to two different Zn(II) respectively; Along the b-axis, adjacent Zn(II) are connected by NCLA 2- O6 and O4 on the ligand are connected to form a 1D chain. The two adjacent 1D chains are arranged symmetrically. Two adjacent bib ligands are connected to the adjacent 1D chains through cross-linking. Through the above connection method, they extend infinitely in the b-axis direction to form a two-dimensional layered structure. The two-dimensional layered structure is stacked with each other through intermolecular hydrogen bonding interactions C6—H6···O2 and C22—H22···O2 to form a 3D framework.
2. The zinc amino acid complex crystalline material according to claim 1, characterized in that: From the perspective of framework connection construction, the crystal structure of the zinc amino acid complex crystal material NCLA-Zn belongs to the monoclinic system. C 2 space group, unit cell parameters are: a=20.023(3) Å, b=10.9307(15) Å, c=15.053(2) Å, α =90°, β = 128.961(3)°, γ =90°.
3. A method for preparing the zinc amino acid complex crystal material according to any one of claims 1 to 2, comprising the following steps: The metal salt ZnCl2, the main ligand N-benzyloxycarbonyl-L-aspartic acid and the auxiliary ligand bib were weighed and placed in a closed container, and a mixed solution of CH3OH and H2O was added to carry out a heating reaction. After the system slowly cooled to room temperature, a white block complex NCLA-Zn was obtained.
4. The method for preparing the zinc amino acid complex crystalline material according to claim 3, wherein: The molar ratio of ZnCl2 to N-benzyloxycarbonyl-L-aspartic acid is 1:(1-1.5); The molar ratio of ZnCl2 to 1,4-bis(1-imidazolyl)benzene is 1:(1.23-1.85).
5. The method for preparing the zinc amino acid complex crystalline material according to claim 3, characterized in that: The volume ratio of CH3OH / H2O in the mixed solution of CH3OH and H2O is 1: (1-1.25), and the volume of the mixed solution is limited to 9 ml of the mixed solution for every 0.1 mmol of ZnCl2.
6. The method for preparing the zinc amino acid complex crystalline material according to claim 3, characterized in that: The heating temperature is 85-100°C and the reaction time is 48-84 hours.
7. Use of the zinc amino acid complex crystal material as described in any one of claims 1 to 2 in solvent recognition.
8. A zinc amino acid complex crystalline material as claimed in any one of claims 1 to 2 in recognizing Fe 3+ The application of the invention is non-disease treatment and disease diagnosis.
9. Use of the zinc amino acid complex crystal material as described in any one of claims 1 to 2 in identifying antibiotics.
Citation Information
Patent Citations
Zinc-based double-ligand coordination polymer crystal material as well as preparation method and application thereof
CN118496517A
Zwitterionic zinc(II) carboxylate compounds and their use
US20180057512A1